2001
DOI: 10.1097/00000539-200110000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Physiologic Hepatic Blood Flow Control (“Hepatic Arterial Buffer Response”) During CO2-Pneumoperitoneum in the Rat

Abstract: We investigated the effect of CO2-pneumoperitoneum on liver blood flow, hepatic tissue oxygenation (PO2) and liver enzyme release. CO2-insufflation reduces portal venous flow without a compensatory increase of hepatic arterial flow ("hepatic arterial buffer response"), resulting in reduced hepatic PO2 and increased ratios of serum alanine aminotransferase to serum aspartate aminotransferase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 24 publications
4
57
0
3
Order By: Relevance
“…Hydropic degeneration, a reversible lesion found in the specimens analyzed in this study, may be explained mainly by decreased portal blood flow during exposure to pneumoperitoneum, either by vascular compression or decreased venous return due to the high intra-abdominal pressure 19 . The lesions found in both postoperative periods (POD3 and POD7) are in agreement with those reported in previous studies, in which the liver had periods of ischemia and reperfusion [19][20][21] . In addition to ischemic events during gas insufflation, other factors, such as the use of anesthetic drugs and the presence of toxins, also trigger vacuolar degeneration.…”
Section: Effects Of Carbon Dioxide Pneumoperitoneum On Hepatic and Resupporting
confidence: 92%
See 1 more Smart Citation
“…Hydropic degeneration, a reversible lesion found in the specimens analyzed in this study, may be explained mainly by decreased portal blood flow during exposure to pneumoperitoneum, either by vascular compression or decreased venous return due to the high intra-abdominal pressure 19 . The lesions found in both postoperative periods (POD3 and POD7) are in agreement with those reported in previous studies, in which the liver had periods of ischemia and reperfusion [19][20][21] . In addition to ischemic events during gas insufflation, other factors, such as the use of anesthetic drugs and the presence of toxins, also trigger vacuolar degeneration.…”
Section: Effects Of Carbon Dioxide Pneumoperitoneum On Hepatic and Resupporting
confidence: 92%
“…The reduction of microcirculation causes changes in immune responses, as well as in Kupffer cells and hepatocyte energy metabolism 20 . Recent studies found alternative explanations to changes in both hepatic function and morphology.…”
Section: Effects Of Carbon Dioxide Pneumoperitoneum On Hepatic and Rementioning
confidence: 99%
“…Consequently, it is not surprising that IAH has also been shown to have detrimental effects on the liver. Specifically, the presence of IAH is known to reduce the blood flow in both the hepatic artery (HA) and the portal vein (PV), thus compromising the liver's physiological capacity to regulate its blood flow (9,18). Furthermore, along with these hemodynamic alterations, IAH has also been shown to result in varying degrees of hepatocyte necrosis, as well as impaired hepatic energy metabolism (19)(20)(21).…”
Section: Abstract Background: While Reduction Of Portal Venous (Pv) mentioning
confidence: 99%
“…To date lower pressure models [39,40] , low-pressure pneumoperitoneum with intermittent deflation at distinct time points [41] and IPC have been attempted to reduce ischemic injury regarding pneumoperitoneum. Many human and animal studies have investigated the effects of increasing intraabdominal pressures (IAP) during laparoscopy and the benefits of low IAP.…”
Section: Iri Secondary To Laparoscopic/robotic Pneumoperitoneummentioning
confidence: 99%